Targeted control of supporting pathways in paclitaxel biosynthesis with CRISPR-guided methylation - Brzycki Newton, Cassandra; Young, Eric M.; Roberts, Susan C. (Frontiers in Bioengineering and Biotechnology, 2023)
Plant cell culture biomanufacturing is rapidly becoming an effective strategy for production of high-value plant natural products, such as therapeutic proteins and small molecules, vaccine adjuvants, and nutraceuticals. Many of these plant natural products are synthesized from diverse molecular building blocks sourced from different metabolic pathways. Even so, engineering approaches for increasing plant natural product biosynthesis have typically focused on the core biosynthetic pathway rather than the supporting pathways. Here, we use both chemical inhibitors and CRISPR-guided DNA methylation to control flux through the phenylpropanoid pathway in Taxus chinensis, which contributes a phenylalanine derivative to the biosynthesis of paclitaxel (Taxol), a potent anticancer drug. For chemical inhibition of the phenylpropanoid biosynthetic pathway, we treated Taxus chinensis plant cell cultures with piperonylic acid and caffeic acid, which inhibit the second and third committed steps in phenylpropanoid biosynthesis: cinnamate 4-hydroxylase (C4H) and 4-coumaroyl-CoA ligase (4CL). Through the synergistic action of both inhibitors and precursor feeding of exogenous phenylalanine, we achieve a 3.5-fold increase in paclitaxel biosynthesis and a similar reduction in production of total flavonoids and phenolics. Further, we observed perturbations to both activity and expression of phenylalanine ammonia-lyase (PAL), the first committed step in the pathway, illustrating the complex transcriptional co-regulation of these first three pathway steps. To more directly inhibit this key regulatory step in the pathway, we knocked down expression of PAL using a CRISPR-guided plant DNA methyltransferase (NtDRM) to increase DNA methylation in the region upstream of the PAL coding sequence, resulting in over a 25-fold increase in paclitaxel accumulation. These results highlight the importance of controlling the metabolic flux of supporting pathways in natural product biosynthesis and demonstrate CRISPR-guided methylation as an effective method for metabolic engineering in plant cell culture. Ultimately, this work demonstrates a powerful method for rewiring plant cell culture systems into next-generation chassis for production of societally valuable compounds.